2021
DOI: 10.1186/s13690-020-00517-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of non-prescribed antibiotics; prevalence estimates in low-and-middle-income countries. A systematic review and meta-analysis

Abstract: Background The global increase in the utilization of non - prescribed antibiotics (NPA), is concerning, with high persistence within the low and middle-income countries (LMICs). With a negative impact on the health of individuals and communities the use of NPA paves the way to the  propagation of superbugs that potentially predisposes to changes in bacterial resistance patterns, antibiotic resistance (AR) and antimicrobial resistance (AMR). This study aimed at estimating through a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…The use of antibiotics without prescription is salient worldwide, with a pooled prevalence exceeding 75% in low- and middle-income countries [ 5 ], and reaching 66% in some regions of high-wealth countries such as the United States [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of antibiotics without prescription is salient worldwide, with a pooled prevalence exceeding 75% in low- and middle-income countries [ 5 ], and reaching 66% in some regions of high-wealth countries such as the United States [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike high-income countries, non-prescribed antibiotics (NPA) (i.e., the use of leftover antibiotics, the use of antibiotics recommended by pharmacy staffs, sharing antibiotics with families or friends [ 24 ]) are easy to access in LMICs [ 18 , 25 ], associated with the lack of robust mechanisms of health education and enforcement measures to control the unnecessary and unreasonable use of antibiotics [ 24 , 26 ]. Moreover, insufficient and inconsistent knowledge and attitudes toward antibiotic use, high expectations on the curative effect of antibiotics, and poor quality of healthcare facilities, are factors driving inappropriate use of antibiotics [ 24 ]. Regarding the above gaps in the prevalence of PSMA around the world and various factors influencing the utilization of antibiotics, we therefore hypothesis that the practices of PSMA may differ among parents of different nationalities in China.…”
Section: Introductionmentioning
confidence: 99%
“…Another review estimated that the mean use of leftover antibiotics worldwide is 29%, and that of compliance with antibiotic therapy is only 62% [5]. A recent meta-analysis of studies from low-and middle-income countries found that the pooled prevalence of non-prescribed use of antibiotics is considerably high (78%) in these countries [6]. Antibiotic misuse is also frequent in high-income countries, including the United States where the prevalence of antibiotic use without prescription is as high as 66% in some instances, and that of storage of antibiotics for future use ranges between 14 and 48% [7].…”
Section: Introductionmentioning
confidence: 99%